2021
DOI: 10.1021/acs.jafc.1c04032
|View full text |Cite
|
Sign up to set email alerts
|

Aged Ripe Pu-erh Tea Reduced Oxidative Stress-Mediated Inflammation in Dextran Sulfate Sodium-Induced Colitis Mice by Regulating Intestinal Microbes

Abstract: Ripened pu-erh tea has the biological activity of antioxidation and anti-inflammation, which inhibits the related parameters of colitis. However, the role of storage-induced changes in bioactive ingredients of ripened pu-erh tea in colitis remains unclear. In this study, 3.5% dextran sulfate sodium-induced colitis mice were treated with 10 mg/kg bw/day extracts, aged 14 years (P2006) and unaged (P2020) ripened pu-erh tea, respectively, for 1 week. We found that ripened pu-erh tea, especially P2006, inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 66 publications
4
58
1
Order By: Relevance
“…Meanwhile, TB elevated the Prevotellaceae family and Alloprevotella genus level in rats which consumed a high-fat and high-sugar diet [ 31 , 53 ]. Our data aligns with previous studies that the administration of TB enriched SCFA producing Prevotellaceae family and Alloprevotella genus in the AOM/DSS model [ 54 ]. Short chain fatty acids (SCFA) in the gut, mainly consisting of acetate, propionate, and butyrate, have shown regulatory effects on CRC by alleviating colon inflammation, strengthening the intestinal barrier and regulating the survival of both normal and cancerous colon cells [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, TB elevated the Prevotellaceae family and Alloprevotella genus level in rats which consumed a high-fat and high-sugar diet [ 31 , 53 ]. Our data aligns with previous studies that the administration of TB enriched SCFA producing Prevotellaceae family and Alloprevotella genus in the AOM/DSS model [ 54 ]. Short chain fatty acids (SCFA) in the gut, mainly consisting of acetate, propionate, and butyrate, have shown regulatory effects on CRC by alleviating colon inflammation, strengthening the intestinal barrier and regulating the survival of both normal and cancerous colon cells [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…It seems a there is a possible involvement of the gut-liver axis through the LPS/TLR-4/pro-inflammatory cytokines axis in the pathogenesis of inflammatory processes. Our lab's early studies have shown that the reduction of intestinal inflammation and liver toxicity by tea (Camella sinensis) and hawk tea (Litsea coreana) is due to the reshaping of gut microbes [17,23,54,84], which further supported the finding reported in this paper that the ALD-mediated intestinal microorganism composition affects intestinal and liver inflammation. The intestinal-flora-disorder-mediated activation of TLR4 signaling pathways aggravates lipid metabolic disorders, further causing liver lipid deposition.…”
Section: Discussionsupporting
confidence: 84%
“…The process of Western blot analysis refers to previous research methods of our laboratory [23]. The liver tissue of mice was washed with cold phosphate buffer solution (PBS) and then treated with a RIPA buffer (RIPA; Servicebio, Wuhan, China) containing a protease inhibitor cocktail.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Besides, Roseburia can regulate the immune system of individuals, and decreases in UC patients (Zhang et al, 2017). Lachnospiraceae has been well recognized as a producer of SCFAs and an inducer of regulatory T cells (Yilmaz & Juillerat, 2019) and Lachnospiraceae_NK4A136_group is an SFCAs-producing bacteria as well, which is related to butyric acid production (Hu et al, 2021). In addition to serving as a source of nutrition for intestinal epithelial cells, SCFAs can also increase the expression of MUC2 and restore the protective effect of the mucus layer against external injury (Buisinea et al, 2001).…”
Section: Discussionmentioning
confidence: 99%